2010
DOI: 10.1097/prs.0b013e3181c2a3b4
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Risk for Venous Thromboembolism in Abdominal Contouring Surgery: A Systematic Review of the Literature

Abstract: Circumferential abdominoplasty and abdominoplasty performed in combination with an intraabdominal procedure were demonstrated to have significantly increased risk for venous thromboembolism. Patients undergoing these procedures should be risk stratified and have perioperative prophylaxis managed accordingly. It is suggested that both of these operations be placed into a higher exposing risk category within the modified Davison-Caprini risk assessment model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 115 publications
0
39
0
2
Order By: Relevance
“…In fact, the modified Davison-Caprini risk-assessment model suggests that virtually every patient who undergoes abdominoplasty would require chemoprophylaxis. 15 In our study, no deep venous thrombosis or pulmonary emboli were observed. Although we did not specifically review patient risk factors or modes of prophylaxis, our routine was to advise discontinuation of hormone therapy when practical, use sequential compression devices (begun prior to induction) on all patients, and have patients ambulate in an upright (nonflexed) position early after surgery.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In fact, the modified Davison-Caprini risk-assessment model suggests that virtually every patient who undergoes abdominoplasty would require chemoprophylaxis. 15 In our study, no deep venous thrombosis or pulmonary emboli were observed. Although we did not specifically review patient risk factors or modes of prophylaxis, our routine was to advise discontinuation of hormone therapy when practical, use sequential compression devices (begun prior to induction) on all patients, and have patients ambulate in an upright (nonflexed) position early after surgery.…”
Section: Discussionmentioning
confidence: 73%
“…14,15 We initially employed the PTS technique in a small series (n = 76) of abdominoplasties reported in 2000. 12 Other investigators, including Baroudi and Ferreira, 13 Georgiade, 16 and LeLouran and Pascal, 17 have used similar suture fixation techniques in abdominoplasty.…”
mentioning
confidence: 99%
“…Patients undergoing circumferential procedures of the lower trunk should always be considered to be at high risk of thromboembolism [81,82]. Hatef [51] found that Based on this review, we strongly recommend chemoprophylaxis associated with early ambulation and the use of compression stockings (standard patients) or pneumatic stockings (high-risk patients).…”
Section: Thromboprophylaxismentioning
confidence: 98%
“…The leading theory regarding the increased incidence of venous thromboembolism relates to the increased intra-abdominal pressure [22]. As tightening the abdominal wall through an ABP would increase intra- [23].…”
Section: Discussionmentioning
confidence: 99%